2017
DOI: 10.17933/bpostel.2017.150102
|View full text |Cite
|
Sign up to set email alerts
|

Status dan Perkembangan Proyek Loon Terkini [Present Status and Development of Loon Project]

Abstract: This study is conducted to gather illustration related to recent status and development of Project Loon in different countries A B S T R A KKata kunci : Poyek Loon Lisensi frekuenisi Perizinan ruang udara Studi ini dilakukan untuk memperoleh gambaran terkait status dan perkembangan Proyek Loon di berbagai negara saat ini dari berbagai aspek hingga awal tahun 2017. Studi ini menggunakan pendekatan kualitatif dan studi literatur. Hasil penelitian menunjukkan bahwa setelah Google melakukan trial Loon di Selandia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Diah Yuniarti and Hilarion Hamjen in 2017 discussed the development of the Loon Project in several countries. The study concluded that balloon experiments in several countries experienced problems mainly in licensing, frequency allocation and airspace [13].…”
Section: 3related Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Diah Yuniarti and Hilarion Hamjen in 2017 discussed the development of the Loon Project in several countries. The study concluded that balloon experiments in several countries experienced problems mainly in licensing, frequency allocation and airspace [13].…”
Section: 3related Researchmentioning
confidence: 99%
“…Not only that, Google's balloon is also equipped with electronic devices ISSN 2085-4811, eISSN: 2579-6089 such as solar panels that function as chargers that guarantee electronic devices can still work for months. As the name suggests, what distinguishes the project loon from other HAP technology is the use of a giant balloon with a length of 15 meters and a width of 12 meters as a component that makes it fly [13]. The balloon is termed as a cover filled with helium gas which is equipped with an automatic system for pumping or releasing air following the ambient temperature.…”
Section: 2project Loonmentioning
confidence: 99%
See 1 more Smart Citation